Local electrochemical control of hydrogel microactuators in microfluidics. (29th June 2018) - Engel, Leeya; Liu, Chengming; Hemed, Nofar Mintz; Khan, Yasser; Arias, Ana Claudia; Shacham-Diamand, Yosi; Krylov, Slava; Lin, Liwei
Abstract: Due to the complexity of a chemo-electro-mechanical system and the need for a wet environment, to date, few devices fully integrate hydrogels with microelectromechanical systems. In this paper, we demonstrate the use of inkjet-printed gold electrodes integrated in microfluidic channels to alter the morphology of electroactive polymer hydrogels, cross-linked in situ . Microfluidics is a convenient platform for integrating hydrogels with microsystems as it provides a means for encapsulating electrolytic environments, while maintaining UV transparency. Printed electronics provide a new method for rapid prototyping of electrodes on flexible substrates for electrical control of electroactive polymer microsystems. We attribute the observed actuation to electrochemically-induced pH variations in the vicinity of the printed anode and cathode which diffuse into the hydrogel. Response to pH was verified by exposing the hydrogel to various pH conditions in control experiments without applied electrical bias. This work demonstrates a new, integrated, polymer-based, rapid prototyping approach to building flexible electroactive hydrogel systems which can benefit microfluidic valves, biomimetics, electrochemical sensors and artificial muscles.